Immunogenicity of various variants of Ebola and Marburg virus glycoprotein genes in recombinant adenoviral vectors - T. A. Ozharovskaia; O. V. Zubkova; O. Popova; A. V. Kovyrshina; P. P. Goldovskaya; I. V. Vavilova; I. V. Dolzhikova; E. I. Ermolova; M. S. Kunda; N. N. Ryzhova; O. L. Voronina; D. N. Shcherbinin; et al. (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODUCTION. Marburg and Ebola viruses cause severe haemorrhagic fever in humans and primates. Currently, there are no licensed prophylactic vaccines that can simultaneously prevent the spread or reduce the severity of both diseases caused by these filoviruses. The development of effective prophylactic vaccines requires studies aimed at selecting the most immunogenic forms of protective antigens.AIM. This study aimed to evaluate humoral immune induction in animals after administration of recombinant adenoviral vectors expressing various forms of Ebola and Marburg virus glycoproteins (GPs).MATERIALS AND METHODS. Samples of recombinant human adenovirus type 5 (rAd5) were obtained using homologous recombination in Escherichia coli, growth in HEK293 cells, and purification by CsCl gradient ultracentrifugation. The resulting rAd5 samples were characterised in terms of their identity (PCR and whole-genome sequencing), the concentration of viral particles (fluorescence spectroscopy), and the concentration of infectious viral particles (TCID50 assay). Enzyme-linked immunosorbent assay (ELISA) was used to evaluate the GP-specific IgG titres in the sera of immunised mice.RESULTS. The authors constructed rAd5 samples, and each construct contained an expression cassette with a GP gene form encoding a full-length GP, a GP without the mucin-like domain, or a GP without both the glycan cap and the mucin-like domain. Each of these forms was studied using the GPs of four filoviruses, including Zaire Ebola virus, Sudan Ebola virus, Bundibugyo Ebola virus, and Marburg virus. Neither of the forms had a critical effect on the rAd5 replicative capacity. Three weeks after immunisation, the highest GP-specific IgG production was induced by the rAd5 samples encoding either the full-length GP or the GP without the mucin-like domain. The GP without both the glycan cap and the mucin-like domain was the least immunogenic antigen regardless of the filovirus species.CONCLUSIONS. The most promising constructs for the development of filovirus vaccines based on recombinant adenoviral vectors are the constructs that include the genes encoding the fulllength GP or the GP without the mucin-like domain.